2014
DOI: 10.1111/1556-4029.12547
|View full text |Cite
|
Sign up to set email alerts
|

Anthropological Facial Approximation in Three Dimensions (AFA3D): Computer‐Assisted Estimation of the Facial Morphology Using Geometric Morphometrics

Abstract: This study presents Anthropological Facial Approximation in Three Dimensions (AFA3D), a new computerized method for estimating face shape based on computed tomography (CT) scans of 500 French individuals. Facial soft tissue depths are estimated based on age, sex, corpulence, and craniometrics, and projected using reference planes to obtain the global facial appearance. Position and shape of the eyes, nose, mouth, and ears are inferred from cranial landmarks through geometric morphometrics. The 100 estimated cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 41 publications
2
68
0
1
Order By: Relevance
“…Analysis of FSTT [8] in correspondence to landmark locations showed that males generally had greater values than females, and that Body Mass Index (BMI) had strong influence of FSTT. Similarly, Guyomarc'h et al indicated that corpulence had the major effect on soft-tissue thicknesses, compared to age, sex, and ethnicity [13]. Body mass and weight have also be taken into consideration by Parks et al, who, given the documented prevalence of obesity in U.S.A. area, purposely assembled U.S. population to consider escalating weight of them [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of FSTT [8] in correspondence to landmark locations showed that males generally had greater values than females, and that Body Mass Index (BMI) had strong influence of FSTT. Similarly, Guyomarc'h et al indicated that corpulence had the major effect on soft-tissue thicknesses, compared to age, sex, and ethnicity [13]. Body mass and weight have also be taken into consideration by Parks et al, who, given the documented prevalence of obesity in U.S.A. area, purposely assembled U.S. population to consider escalating weight of them [10].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue depths were estimated also by Guyomarc'h et al depending on age, sex, and corpulence by working on 87 hard-tissue and 102 soft-tissue landmarks. Among the skin landmarks adopted for this study, some were manually positioned on face, others were projected on the skin from the corresponding osseous landmark [13]. Parks et al, supported by Federal Bureau of Investigation (FBI) Laboratory Division, aimed at building a detailed tissue depth database among 25 landmarks and compared it with previous relevant studies [10].…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations